INOS/Arginase-1 expression in the pulmonary tissue over time during Cryptococcus gattii infection. Issue 2 (February 2020) - Oliveira-Brito, Patrícia Kellen Martins; Rezende, Caroline Patini; Almeida, Fausto; Roque-Barreira, Maria Cristina; da Silva, Thiago Aparecido
Inhalation of Cryptococcus gattii yeasts (causing cryptococcosis) triggers an anti-cryptococcal immune response initiated by macrophages, neutrophils or dendritic cells, and the iNOS expressed by various cells may regulate the function and differentiation of innate and adaptive immune cells. Here, we evaluated the effect of progression of C. gattii infection on the host innate immune response. C. gattii infection in BALB/c mice spreads to several organs by 21 d post infection. The numbers of neutrophils and lymphocytes in the peripheral blood of C. gattii –infected mice were remarkably altered on that day. The frequency of CD11b + cells and cell concentrations of CD4 + and CD8 + T cells was significantly altered in the pulmonary tissue of infected mice. We found a higher frequency of CD11b + /iNOS + cells in the lungs of infected mice, accompanied by an increase in frequency of CD11b + /Arginase-1 + cells over time. Moreover, the iNOS/Arginase-1 expression ratio in CD11b + cells reached its lowest value at 21 d post infection. In addition, the cytokine micro-environment in infected lungs did not show a pro-inflammatory profile. Surprisingly, iNOS knock-out prolonged the survival of infected mice, while their pulmonary fungal burden was higher than that of infected WT mice. Thus, C. gattii infection alters the immune response in the pulmonary tissue, and iNOS expression may play a key role in infection progression.